Correlation between changes in brain natriuretic peptide and echocardiographic features in persistent pulmonary hypertension of newborn. (2nd July 2020) - Fu, Lin; Zhang, Xiaoshan
Abstract: Objective: To investigate the correlation between changes in brain natriuretic peptide (BNP) and echocardiographic features in persistent pulmonary hypertension of newborn (PPHN). Patients and methods: A total of 76 patients with PPHN treated in our hospital from March 2017 to February 2018 were divided into mild group ( n = 33), moderate group ( n = 22) and severe group ( n = 21) according to the pulmonary arterial systolic pressure, and they were compared with 30 normal newborns (control group) during the same period. All newborns underwent echocardiography, the BNP level was detected, and the correlation between echocardiographic features and BNP changes was analyzed. Results: The BNP level in control group was significantly lower than those in PPHN groups, and it was constantly increased from mild group to severe group ( p <.05). There were no significant differences in left atrial diameter (LA) and left ventricular diameter (LV) among groups ( p >.05), while there were significant differences in the right atrial diameter (RA), right ventricular diameter (RV) and peak velocity of tricuspid regurgitation (VTR) ( p <.05). BNP had no correlations with LA and LV ( p >.05), but had positive correlations with RA, RV and VTR ( r = 0.527, 0.503 and 0.524, p <.05). Conclusion: The BNP level of patients with PPHN increases with the increasing severity of disease. BNP has close correlations with echocardiographic features of neonatal patients. Predicting the BNP changes via echocardiography is of certain value in guiding the clinical treatment.